PRAPERADILAN SETELAH PUTUSAN MK.NO. 21/PUU-XII/2014 (Lex Jurnalica, 2018)
AbstractPre-trial institution is a new institution which is regulated in the law no.8 of 1981 on the criminal procedure law abbreviated KUHAP (Books of Criminal Procedure Code). Then in accordance with the development of society and the development of criminal law, the constitutional court of the Repblik of Indonesia in its decision no. 21/PUU-XII/2014 dated October 30, 2014, has expanded the understanding of the pre-trialset forth in article 1 point 10 and article 77 of the Criminal Procedure Code (KUHAP). However, in its journey from pre-trial institutions has not fulfilled the hope of justice seekers, especially for victims of crime or those who feel aggrieved due to the crime itself. Considering that many pre-trial applications rejected by pre-trial judges imndicate thet pre-trial institutions’ arrangements in legislation, especially the Criminal Procedure Code, have not been sufficiently effective and efficient, implying that pre-trial institutions are only to stall the time of the judicial process or to avoid the judicial process which inturn pre-petition in still rejectedby the judge as the case of former chairman of the House of Representatives, Setya Novanto. Likewise for criminal acts that can not be disclosed by the investigator, so many criminal act that can not be revealed by the investigator or the process in long-winded and protracted, thus harming the victim of a criminal act or the party who feel harmed due to the crime is due to experience prolonged injustice like KPK investigator case, Novel Baswedan. Keywords : pre-trial, vonis, constitutional court AbstrakLembaga pra peradilan merupakan lembaga yang baru yang diatur didalam undang-undang no. 8 tahun 1981 tentang hukum acara pidana yang disingkat KUHAP (Kitab Undang-undang Hukum Acara Pidana). Kemudian sesuai dengan perkembangan masyarakat dan perkembangan hukum pidana, Mahkamah Konstitusi Republik Indonesia dalam putusannya no. 21/PUU-XII/2014 tanggal 30 Oktober 2014, telah memperluas pengertian dari pada pra peradilan yang diatur dalam pasal 1 angka 10 dan pasal 77 KUHAP. Namun didalam perjalanannya dari lembaga pra-peradilan tersebut belum memenuhi harapan pencari keadilan terutama bagi korban tindak pidana atau pihak yang merasa dirugikan akibat tindak pidana itu sendiri. Mengingat banyak nya permohonan pra peradilan yang ditolak oleh hakim pra peradilan menunjukkan bahwa pengaturan lembaga pra peradilan didalam peraturan perundang-udangan terutama KUHAP, belum cukup efektif dan efisien, sehingga terkesan lembaga pra peradilan hanya untuk mengulur-ulur waktu dari proses peradilan pidana atau untuk menghindar dari proses peradilan yang pada gilirannya permohonan pra peradilan tersebut tetap ditolak oleh hakim seperti kasus mantan ketua DPR RI, Setya Novanto. Begitu pula bagi tindak pidana yang tidak bisa diungkap oleh penyidik, begitu banyak tindak pidana yang tidak bisa diungkap oleh penyidik atau prosesnya yang bertele-tele dan berlarut-larut, sehingga merugikan korban atau pihak yang dirugikan akibat tindak pidana tersebut yang mengalami ketidak adilan yang berkepanjangan seperti kasus penyidik KPK, Novel Baswedan. Kata kunci : praperadilan, putusan, mahkamah konstitusi